2019
DOI: 10.1051/matecconf/201928908007
|View full text |Cite
|
Sign up to set email alerts
|

The influence of SAPs on chloride ingress in cracked concrete

Abstract: Super Absorbent Polymers (SAPs) have proven to be effective as a self-healing agent for regaining the liquid tightness of cracked concrete. This is due to their large swelling capacity which allows them to (partially) block cracks which are in contact with water or moisture. Additionally, they are able to release this water when the climate becomes drier, thereby promoting the autogenous healing capacity of the concrete matrix. The effect SAPs have on chloride migration into cracked concrete is still unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Concerning the role of superabsorbent polymers (SAP) in self-healing, Van Mullem et al [215] verified the chloride ingress in mortar samples with a crack width of 150 μm with and without SAPs. The healing regime of wet/dry cyles was performed for 28 days before submersion of the specimens in a chloride solution with 150 g L –1 of sodium chloride.…”
Section: Self-healing Under Aggressive Environmental Conditionsmentioning
confidence: 99%
“…Concerning the role of superabsorbent polymers (SAP) in self-healing, Van Mullem et al [215] verified the chloride ingress in mortar samples with a crack width of 150 μm with and without SAPs. The healing regime of wet/dry cyles was performed for 28 days before submersion of the specimens in a chloride solution with 150 g L –1 of sodium chloride.…”
Section: Self-healing Under Aggressive Environmental Conditionsmentioning
confidence: 99%
“…This study focused on self-healing mortar with macrocapsules, but the combination of the water flow test in combination with an active crack width control technique can easily be applied for other healing techniques. Due to the fast execution time, it has, for example already been applied to study the sealing efficiency of superabsorbent polymers [54] and superabsorbent polymers in combination with nanosilica [55].…”
Section: Water Permeability Of Mortar Specimensmentioning
confidence: 99%
“…The first method consisted of a low-head water flow test on prismatic specimens cracked in a threepoint bending test with subsequent active crack width control, because it has been identified that small changes in crack width can result in significant differences with respect to water flow through a crack [22]. To test the stability of the formed healing products at higher water pressures, a high-head water flow test (up until 2 bar) was executed on these specimens [18,23].In the second method cylindrical specimens with the different agents were cracked in a Brazilian splitting test creating specimens with a different crack geometry, i.e. cracks with a constant thickness over the height instead of the more triangular shaped cracks in the prismatic specimens.…”
Section: Introductionmentioning
confidence: 99%